2018
DOI: 10.1002/cam4.1771
|View full text |Cite
|
Sign up to set email alerts
|

An Aurora kinase inhibitor, AMG900, inhibits glioblastoma cell proliferation by disrupting mitotic progression

Abstract: The Aurora kinase family of serine/threonine protein kinases comprises Aurora A, B, and C and plays an important role in mitotic progression. Several inhibitors of Aurora kinase have been developed as anti‐cancer therapeutics. Here, we examined the effects of a pan‐Aurora kinase inhibitor, AMG900, against glioblastoma cells. AMG900 inhibited proliferation of A172, U‐87MG, and U‐118MG glioblastoma cells by upregulating p53 and p21 and subsequently inducing cell cycle arrest and senescence. Abnormal cell cycle p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Both kinases have been reported as the negative prognostic markers in GB 41 , 42 . Consistently, selective inhibitors of Aurora A [e.g., MLN8237 and VX 689 23 , 30 , 41 , 43 ], Aurora B [e.g., AZD1152-HQPA 21 , 22 ], as well as pan-Aurora inhibitors [e.g., AMG900, ZM 447439 44 , 45 ] have been reported effective in GB cell lines as well as mouse models, when administered either as individual compounds, mixtures with temozolomide, or upon combination with irradiation.…”
Section: Discussionmentioning
confidence: 89%
“…Both kinases have been reported as the negative prognostic markers in GB 41 , 42 . Consistently, selective inhibitors of Aurora A [e.g., MLN8237 and VX 689 23 , 30 , 41 , 43 ], Aurora B [e.g., AZD1152-HQPA 21 , 22 ], as well as pan-Aurora inhibitors [e.g., AMG900, ZM 447439 44 , 45 ] have been reported effective in GB cell lines as well as mouse models, when administered either as individual compounds, mixtures with temozolomide, or upon combination with irradiation.…”
Section: Discussionmentioning
confidence: 89%
“…Pan-AURKi AMG900 is one of the furthest developed AURKi, showing promising preclinical [ 34 ] and clinical [ 35 ] activity. AMG900 has also been shown to induce senescence in glioblastoma cells [ 36 ]. AZD1152 (barasertib) has been shown to selectively inhibit AURKB and inhibit tumor growth in a dose-dependent manner in different preclinical xenograft models [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a phthalazinamine-based compound which competitively inhibits binding of ATP to the active site of aurora kinases [ 134 ]. Reports have shown that AMG900 inhibited the growth of glioblastoma cells in vitro ultimately leading to cell cycle arrest and senescence [ 135 ]. In MOLM-13 AML cell line, treatment with AMG900 was linked to inhibition of histone H3 phosphorylation, polyploidy and increased apoptosis with the upregulation of p53 [ 136 ].…”
Section: Targeting Aurkb In Cancermentioning
confidence: 99%